NF-κB-Dependent IFIT3 Induction by HBx Promotes Hepatitis B Virus Replication - Xu, Fengchao; Song, Hongxiao; An, Beiying; Xiao, Qingfei; Cheng, Genhong; Tan, Guangyun (Frontiers in Microbiology, 2019)
Therapeutic administration of type I IFN (IFN-I) is a common treatment option for individuals suffering from hepatitis B virus (HBV) infection. IFN-I therapy, however, has a relatively low response rate in HBV-infected patients and can induce serious side-effects, limiting its clinical efficacy. There is, thus, a clear need to understand the molecular mechanisms governing the influence of IFN-I therapy in HBV treatment in order to improve patient outcomes. In this study, we explored the interactions between HBV and IFITs (IFN-induced proteins with tetratricopeptide repeats), which are classical IFN-inducible genes. Specifically, we found that HBV patients undergoing IFN-I therapy exhibited elevated expression of IFITs in their peripheral blood mononuclear cells (PBMCs). We further observed upregulation in the expressions of IFIT1, IFIT2, and IFIT3 in cells transfected with the pHBV1.3 plasmid, which yields infectious virions in hepatic cells. We additionally found that HBx, which is the only regulatory protein encoded within the HBV genome, activates NF-κB, which in turn directly drives IFIT3 transcription. When IFIT3 was overexpressed in HepG2 cells, HBV replication was enhanced. Together, these results suggest that IFIT genes may unexpectedly enhance viral replication, thus making these genes potential therapeutic targets in patients with HBV.